Beyond Stockholders and Stakeholders: A Plea for Corporate Moral Autonomy - Humber, James M. (Journal of business ethics, 2002)
In order to ensure that corporations act in socially responsible ways. R. Freeman says that firms should be legally required to act in accordance with the directives of a moral theory which he developed especially for business – a theory which has come to be called "normative stakeholder theory" (NST). I argue that NST fails as a moral theory and that this failure indicates: (1) that we should abandon the quest to develop a special moral theory for use in business, and (2) that we should not attempt to impose the use of any moral theory upon business, but rather should allow corporations to determine their moral responsibilities in any way they see fit.